Apakah Learning Start with a Question Efektif Digunakan dalam Microteaching?: Eksperimen pada Calon Guru Sekolah Dasar - Gantina, Nina; Khoiri, Ahmad (Universitas Muhammadiyah Surakarta, 2020)
Prospective Elementary School Teachers have difficulty in understanding the science concepts. Beside, they are generally low in curiosity, passive in discussion, and lack of collaboration on microteaching activities. This study aims to: (1) Reveal how to apply the experimental-based LSQ learning model on microteaching activities for elementary school teacher candidates; (2) Examine the increase in curiosity and understanding the concept of science. The method used is a Quasi-experiment method with purposive sampling technique. The sample are 31 elementary school teacher candidates from Universitas Sains Al Quran, Wonosobo, Indonesia. The data about understanding the concept was collected through a test with 30 questions. The data about curiosity was collected by questionnaires and observation sheets. The results showed that there is an increase in the understanding of the concept based on the gain test of 0.3. Furthermore, based on the t-test of 4.01 and t-table of 1.99 (tcount t-table = 4.01 1.99), LSQ model is effective in increasing the curiosity. Curiosity through the four main skills found, namely: questioning skills, reinforcement, explanation skills, and classroom management. The average result of the competency percentage on LSQ learning is 72% (medium category). LSQ is strongly recommended to be applied by prospective elementary school teachers.